Designing change management for business expansion in a msme (study case of tahu sulthan company) - Hakim, Bachtiar Firdaus Lukman; Sushandoyo, Dedy (Journal of Business and Management, 2020)
Abstract. Micro, Small, and Medium Enterprises is a productive business that is very important in creating jobs and developing the global economy for Indonesia. One of the industries of MSME that encourages economic growth is the food and beverage industry especially in the food processing sector. Klaten Regency is an area located in Central Java that has a variety kind of MSME, one of which is the tofu-making industry, one of the tofu companies that is still running is the Tahu Sulthan company. Tahu Sulthan company is a company that was founded in 2010. This tofu company was founded by Mr. Widoyo and is engaged in the tofu processing industry. The problem that arises and is experienced by this company is that it still does not have a well-organized management system., such as problems with workers, administrative, marketing, operational, sales growth, and competitor pressure. This research was prepared using two models of change management, by using the McKinsey 7s as a model in diagnosing problems. Then, after the solution is obtained, proceed with using Kotter’s 8 Step of Change to implement the change strategyKeywords: Change Management, Micro-Small-and-Medium-Enterprises (MSME), Business Expansion, 7s McKinsey, Kotter ‘s 8 Step of Change Management Model